Attention impedes neural representation of interpolated orientation during perceptual completion. (3rd March 2022) - Mo, Ce; Zhang, Shijia; Lu, Junshi; Yu, Mengxia; Yao, Yujie
Abstract: One of the most remarkable functional feats accomplished by visual system is the interpolation of missing retinal inputs based on surrounding information, a process known as perceptual completion. Perceptual completion enables the active construction of coherent, vivid percepts from spatially discontinuous visual information that is prevalent in real‐life visual scenes. Despite mounting evidence linking sensory activity enhancement and perceptual completion, surprisingly little is known about whether and how attention, a fundamental modulator of sensory activities, affects perceptual completion. Using EEG‐based time‐resolved inverted encoding model (IEM), we reconstructed the moment‐to‐moment representation of the illusory grating that resulted from spatially interpolating the orientation of surrounding inducers. We found that, despite manipulation of observers' attentional focus, the illusory grating representation unfolded in time in a similar manner. Critically, attention to the surrounding inducers simultaneously attenuated the illusory grating representation and delayed its temporal development. Our findings disclosed, for the first time, the suppressive role of selective attention in perceptual completion and were suggestive of a fast, automatic neural machinery that implements the interpolation of missing visual information. Abstract : Perceptual completion enables the active construction of coherent, vivid percepts from spatially discontinuous information prevalent in real‐life visual scenes. We reconstructed the temporal dynamics of the illusory orientation representation that resulted from perceptual completion, which demonstrate, for the first time, the suppressive role of attention and the critical involvement of horizontal connections among early visual neurons in perceptual completion.